The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.6061/clinics/2013(03)oa08
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions to antituberculosis drugs in Manguinhos, Rio de Janeiro, Brazil

Abstract: OBJECTIVES:This study aimed to characterize and estimate the frequency of adverse reactions to antituberculosis drugs in the population treated at the Centro de Saúde Escola Germano Sinval Faria, a primary health care clinic in Manguinhos, Rio de Janeiro City, and to explore the relationship between adverse drug reactions and some of the patients' demographic and health characteristics.METHODS:This descriptive study was conducted via patient record review of incident cases between 2004 and 2008.RESULTS:Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
(27 reference statements)
5
11
0
Order By: Relevance
“…Ramanath et al, reported similar findings with most (92.97%) ADRs showing a possible causal relationship. 21 Similar results have been reported by Damasceno et al 22 Present study had three certain/definite (5.30%) cases in which re-challenge was done and offending drug was found to be pyrazinamide. A study conducted by Verma et al, categorised 9.8% of the cases as definite/severe.…”
Section: Figure 2: Causality Assessment (Who-umc)supporting
confidence: 83%
“…Ramanath et al, reported similar findings with most (92.97%) ADRs showing a possible causal relationship. 21 Similar results have been reported by Damasceno et al 22 Present study had three certain/definite (5.30%) cases in which re-challenge was done and offending drug was found to be pyrazinamide. A study conducted by Verma et al, categorised 9.8% of the cases as definite/severe.…”
Section: Figure 2: Causality Assessment (Who-umc)supporting
confidence: 83%
“…Previous reports of some notable adverse drug reactions include weight increase and hepatotoxicity [29] , [45] , reproductive toxicity [29] , exanthema, hematological [46] among others when RIPE is used either as the sole agent or together. In fact, antituberculosis drug-induced hepatotoxicity has been reviewed [47] .…”
Section: Discussionmentioning
confidence: 99%
“…Another point that can lead to abandonment, and consequently drug-resistance, is the adverse effects that medication brings. In Rio de Janeiro it was possible to find side effects in 22.2% of the people from 0-19 years old (39) .…”
Section: Clinical and Epidemiological Features Of Tuberculosis In Chimentioning
confidence: 99%